ANALISIS PENGARUH PENGENDALIAN INTERNAL TERHADAP PENCEGAHAN FRAUD PADA PT. BANK TABUNGAN NEGARA (PERSERO) KC. AMBON - Angkotta, Anatasia Z; Kainama, Maryoni S; Tomasoa, Theodora F (Program Studi Akuntansi PSDKU Universitas Pattimura di Kabupaten Maluku Barat Daya, 2024)
The aim of this research is to analyze the influence of internal control on fraud prevention at PT Bank State Saving (Persero) KC Ambon. The practical benefit of research is that for companies, it can be used as input in making decisions to apply accounting methods and in improving supervision within the company. The method used in this research uses quantitative research with the aim of finding answers to a phenomenon or question through data processing applications, namely using SPSS Software with the Simple Linear Regression method. The results of this research show that variable Apart from that, the role of internal control at Bank Tabungan Negara (BTN) Persero KC. Ambon is also included in the good category. BTN's internal control in carrying out its duties has used a system that is in accordance with applicable policies, plans, procedures, laws and regulations.